Development of the Textile Industry in Selected Transition Countries of Europe in the Period 1995-2018 - Nikolić, Mirоljub; Radovanović, Olga; Cvetanovic, Slobodan; Despotovic, Danijela Z (Industrija, 2021)
The paper examines the development of the textile industry in nine selected European countries in transition (Bosnia and Herzegovina, Bulgaria, Croatia, the Czech Republic, Hungary, North Macedonia, Romania, Serbia and Slovenia) in the period from 1995 to 2018, which have made the transition to a market economy model with varying degrees of success. The aim is to review the basic trends in the development of the textile industry in these countries by achieving the transition to a market model of business with varying degrees of success, which, among other things, is accompanied by a strong wave of deindustrialization. The interdependence of Textiles and clothing industry value added in manufacturing and GDP pc levels in individual countries was calculated by the exponential correlation procedure. It was stated that these countries based their development in the transition period largely on strengthening trade competitiveness, with the textile industry (Textile fibers, yarn, fabrics and clothing) contributing to a significant export expansion. It turned out that the contribution of the textile industry to the economic growth of the analyzed economies was higher in the earlier stages of their economic development. Also, the results of the research confirmed that the textile industry in these countries has maximized its export potential at lower levels of their GDP pc.
Keywords: textil industry; development; competitiveness; countries in transition